Impact of Green HR Development Practices on Sustainable Workplace Behavior in Bangladeshi Manufacturing Industries: The Moderating Role of Environmental Concern - Uddin, Maeen; Ullah, Md Arif; Nyeema, Jannatul; Chowdhury, Priya; Merina, Munia Akther (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study examines the influence of green human resource development practices-specifically Green Orientation Training (GOT), Environmental Workshops and Seminars (EWS), and On-the-Job Eco-Skill Development (OJESD)-on employees’ Sustainable Workplace Behavior (SWB), with Environmental Concern (EC) as a moderator. It focuses on key manufacturing industries in Bangladesh (i.e., garments, leather, and pharmaceuticals); data collection was conducted via a structured survey and analyzed using PLS-SEM. Findings reveal that GOT and OJESD have a stronger positive impact on SWB (β=0.360, p<0.001, and β=0.305, p=0.000) while EWS shows a comparatively weaker effect. Notably, EC negatively moderates the GOT-SWB relationship (β=-0.111, p=0.016), indicating that basic orientation is less effective for highly concerned employees. Theoretically, this research extends training mechanisms by disintegrating them into three types (e.g., GOT, EWS, and OJESD). The major contribution of the study lies in its strong suggestions for green training initiatives for Bangladesh’s manufacturing industries. It advises managers to prioritize foundational and practical training while customizing programs to avoid redundancy for highly environmentally conscious individuals. It also asserts that green training programs must focus on changing employees’ hearts, not just organizing mundane sessions for external audit compliance.